Key Factors that Strengthen Student Entrepreneurial Intention: A Systematic Literature Review - Wiwik Rahayu; Herlin Setyawan; Ganefri; Asmar Yulastri; Giatman; Hansi Effendi; Dedy Irfan (Universitas Pendidikan Ganesha, 2025)
Entrepreneurial intention among students is increasingly important to reduce the unemployment rate and increase economic growth. The literature review article Key Factors that Strengthen the Entrepreneurial Intention of Students is a research article that aims to find factors that strengthen students' intention in entrepreneurship. The research method used is library research, including searches through Scopus, Harzing's Publish, and Perish. This study uses a comprehensive literature analysis method to evaluate factors such as entrepreneurship education, environmental support (family, friends, and university), practical experience, personal characteristics, and motivation and attitude toward risk. The results show that entrepreneurship education received on campus, access to resources and mentor support, and individual characteristics such as self-confidence and risk-taking courage are the main factors driving students' entrepreneurial intentions. In addition, internal motivation factors and social support also play an essential role in influencing students' decision to choose an entrepreneurial path. The factor of entrepreneurial culture on campus also plays a role as an amplifier of entrepreneurship education. The findings are expected to contribute to academics, educational institutions, and policymakers in designing effective strategies to foster entrepreneurial intention among university students.